Challenges of teaching english to students with hearing disabilities - Suarez Velez, Geovanna Lissette (2024)
Students with hearing impairment represent a challenge to teachers when teaching English, however, it is a topic that does not have much coverage, these students like all students deserve complete and satisfactory teaching, the present research aims to explore and learn about the challenges faced by teachers when teaching English to students with hearing impairment. It involved a sample of English teachers with experience in teaching students with hearing impairments and used qualitative research methods such as one-on-one interviews. The project aimed to delve into the challenges faced by each of the teachers in teaching English to students with hearing impairments and to inquire into their experiences and methods used to meet this challenge. The results of this research contributed to inclusive education and provided accurate information to teachers and curriculum developers seeking to improve education for students with hearing impairments.